(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Our previous studies indicated that recombinant rabies viruses expressing chemokines and cytokines (including GM-CSF) could enhance the immunogenicity by inducing innate immunity and recruiting/activating dendritic cells and B cells. In this study, bacterial flagellin was cloned into the rabies virus genome and recombinant virus rLBNSE-Flic was rescued. To compare the immunogenicity of rLBNSEFlic with recombinant virus expressing GM-CSF (rLBNSE-GMCSF), mice were immunized with each of these recombinant rabies viruses by i.m. or the oral route. The parental virus (rLBNSE) without expression of any foreign molecules was included for comparison. The i.m.-immunized mice were bled at three weeks after the immunization for the measurement of virus neutralizing antibodies (VNA) and then challenged with 50 LD50 CVS-24. The orally immunized mice were boostered after three weeks and then bled and challenged one week after the booster immunization. It was found that both the recombinant viruses LBNSE-GMCSF and LBNSE-Flic induced higher levels of VNA and protected more mice against rabies challenge than the parental rLBNSE in both the i.m.- and the orally immunized groups. Together, these studies suggest that recombinant rabies viruses expressing GM-CSF or flagellin are better vaccines than the parent virus for both parental and oral immunizations, most likely by recruiting/activating dendritic cells.